Nutritional intake and overall diet quality of female soccer players before the competition period - Santos, Daniel dos [UNESP]; Silveira, Jacqueline Queiroz da [UNESP]; Cesar, Thais Borges [UNESP] (Pontificia Universidade Catolica Campinas, 2016)
Objective To assess the dietary intake and overall diet quality of female soccer players before the competitive games. Methods This descriptive and cross-sectional study included 21 women aged 20.8 +/- 4.5 years from a professional soccer team. Their nutritional status and dietary adequacy during the training period, before competition season, were assessed. Dietary intake was assessed by three 24-hour recalls, one food frequency questionnaire, and the Healthy Eating Index, an overall diet quality index based on food group intake. Results The athletes have shown proper nutritional status, but a diet deficient in energy due largely to low carbohydrate intake. On the other hand, the intakes of protein, fatty acids, and sodium were above the recommended intakes, even for athletes. Diet quality assessment by the Healthy Eating Index - 2010 resulted in a mean score of 54.6 points of a maximum of 100, indicating a need of improving the overall diet quality. Conclusion The study found that the dietary patterns of female football players were both quantitatively and qualitatively inappropriate. A nutritional intervention is indicated to improve diet quality, with the inclusion of various foods, such as whole grains, fruits, vegetables, dairy products, and better protein quality, along with a reduction in saturated fats, sodium, and added sugar.
Keywords: Nutritional assessment; Healthy Eating Index; Soccer; Women